The Effects of Three Types of Prophylactic Knee Bracing on Abduction Angle and Abduction Moment of Knee Joint in Foot Rotation Positions during Single Leg Landing in Anterior Cruciate Ligament Injury - Hossein Goldashti; Mansour Eslami; Mohammad Taghipour (مجله پژوهش در علوم توانبخشی, 2019)
landing movements. The aim of the present study was to investigate the effect of three preventive knee joints on the variables of abduction angle and abduction moment in three types of single leg landing in healthy young people.